Analysis of Roof Tile Defective Products Using the Seven Tools Method in PT. XYZ - Ihsan, Ikhwanul; Sugiyono, Sugiyono (Journal of Sustainable Economic and Business, 2025)
Objectives: This study aims to analyze and reduce the number of defective products produced by PT XYZ which is 3% per month. This research uses a quantitative descriptive method as a method used to find the root causes. The purpose of this study is to determine the number of defective products that occur, the factors that cause them, and provide recommendations for improvement to improve the quality of roof tile products. Methodology: This research uses the Seven Tools method which includes check sheets, histograms, control charts, pareto diagrams, and fishbone diagrams to identify and analyze the causes of defective roof tile products. Findings: Check sheets help in the collection and analysis of defect data. Stratification shows that the most common defect is Face Crack, which accounts for 39.01% of the total defects. Conclusion: The pareto diagram shows that Face Crack and Lap Fault are the two most dominant types of defects. The histogram shows that the total product defects are 113,138 for the Face Crack category. The control map shows that the dominant product defects are outside the control limits, indicating the need for improvements to the production process. The fishbone diagram identifies the factors affecting product defects are human, machine, environment, and material.